2013
DOI: 10.1134/s0006297913070080
|View full text |Cite
|
Sign up to set email alerts
|

Lectins of marine hydrobionts

Abstract: Data from the literature and results of our research on lectins isolated from some kinds of marine hydrobionts such as clams, ascidians, sea worms, sponges, and algae are presented in this review. Results of comparative analysis of the basic physicochemical properties and biological activity of lectins isolated from various sources are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…Therefore, the high expression of the serine protease inhibitor in healthy clams supports its involvement in M. mercenaria ’s resistance against QPX, likely by inhibiting the activity of parasite proteases. Moreover, a pathogen recognition protein (c-type lectin domain family 10 member A-like) was significantly higher in healthy clams as compared to diseased animals, which may also contribute to clam resistance against QPX by promoting microbial recognition and encapsulation [ 128 ]. Previous studies demonstrated that clam genetic background affects M. mercenaria resistance toward QPX [ 4 , 129 , 130 ], therefore immune-related transcripts specifically associated with healthy clams represent excellent candidates as molecular markers for further research on screening and breeding QPX-resistant M. mercenaria strains.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the high expression of the serine protease inhibitor in healthy clams supports its involvement in M. mercenaria ’s resistance against QPX, likely by inhibiting the activity of parasite proteases. Moreover, a pathogen recognition protein (c-type lectin domain family 10 member A-like) was significantly higher in healthy clams as compared to diseased animals, which may also contribute to clam resistance against QPX by promoting microbial recognition and encapsulation [ 128 ]. Previous studies demonstrated that clam genetic background affects M. mercenaria resistance toward QPX [ 4 , 129 , 130 ], therefore immune-related transcripts specifically associated with healthy clams represent excellent candidates as molecular markers for further research on screening and breeding QPX-resistant M. mercenaria strains.…”
Section: Resultsmentioning
confidence: 99%
“…Marine lectins are structurally diverse, and their unique structures have a number of potential uses in biomedical applications. Although more than 300 species of marine lectins have been found, most of these investigations have focused on those with biomedical applications as antibacterial, antifungal, antiviral, antitumour, antinociceptive and anti-inflammatory agents 8 , 29 . Lectins are characterized as immunomodulatory agents and can induce the production of certain cytokines and reactive species to induce efficient immune responses against tumours or microbial infections 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Genes of marine invertebrates are considered to closely reflect those of the common ancestor(s) of animals, and are therefore useful for elucidating fundamental evolutionary mechanisms, and for development of molecular tools in biomedical fields. Many novel types of lectins have been found in marine invertebrate species (13)(14)(15)(16), and some of these lectins have been shown to inhibit growth of viruses (17,18), regulate development of symbiotic/pathogenic microorganisms (19,20), or affect mammalian cell cycle (21)(22)(23)(24). D-galactose (Gal) evidently emerged as an important monosaccharide later in evolutionary time than glucose, fructose, or mannose, and therefore plays key roles in cellular recognition (25).…”
Section: A Introductionmentioning
confidence: 99%